الاتحاد المصرفي الأوروبي كضرورة لاستكمال التكامل النقدي والوقاية من الأزمات المالية - بوطورة, فضيلة; سمايلي, نوفل (جامعة الوادي - University of Eloued, 2018)
أظهرت أزمات البنوك والديون السيادية في منطقة الأورو فجوات عميقة في هيكل النظام المالي الأوروبي التي تجعله عرضة لأزمات مستقبلية، وفي نفس الوقت أدى عجز الموازنات العامة المستمر في هذه الدول إلى ارتفاع شديد في الديون السيادية، وخلال الأزمة المالية العالمية اضطرت بعض الدول الأوروبية إلى تقديم حزم إنقاذ لنظامها المصرفي، الأمر الذي رفع من مستويات الديون السيادية وأدى في النهاية إلى أزمة الديون السيادية الأوروبية. مما استوجب على صناع القرار في أوروبا ضرورة استكمال بناء التكامل الاقتصادي والنقدي بالوحدة المصرفية منذ نهاية عام 2014 عبر مراحل زمنية متعاقبة إلى غاية عام 2025. It showed crises banks and sovereign debt in the Euro zone deep gaps in the European financial system, which makes it vulnerable to future crises structure, At the same time continuing public budget deficits in these countries has led to a sharp rise in sovereign debt, and during the global financial crisis, some European countries were forced to provide rescue of its banking system packages, which would raise the sovereign debt levels and ultimately led to the European sovereign debt crisis. Which necessitated the decision-makers in Europe and the need to complete the construction of economic and monetary integration of banking unit since the end of 2014 through the successive stages of the period until 2025.
European Banking Union as a Necessity to Complete Monetary Integration and Prevent Financial Crises
مقال
Keywords: البنك المركزي ; الأزمات المالية ; الاتحاد المصرفي; Central Bank ; Financial Crisis ; the Banking Union